2017
DOI: 10.1111/1742-6723.12824
|View full text |Cite
|
Sign up to set email alerts
|

Review article: Paediatric status epilepticus in the pre‐hospital setting: An update

Abstract: Paediatric status epilepticus (SE) is a medical emergency and a common critical condition confronting pre-hospital providers. Management in the pre-hospital environment is challenging but considered extremely important as a potentially modifiable factor on outcome. Recent data from multicentre clinical trials, quality observational studies and consensus documents have influenced management in this area, and is important to both pre-hospital providers and emergency physicians. The objective of this review was t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 41 publications
0
4
0
1
Order By: Relevance
“…Another important aspect of prehospital CSE management, especially in paediatric populations, is dosing. The correct weight-based dose of intramuscular midazolam has been subject to discussion ranging from 0.1 to 0.2 mg/kg4 5 26 and fixed doses of 5 mg for patients weighing from 13 to 40 kg and 10 mg above 40 kg 11 27 28. Incorrect weight-based dosing in the prehospital setting has been an important issue of concern for paramedics29 and in a recent study, a third of treated patients received an incorrect dose 30.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another important aspect of prehospital CSE management, especially in paediatric populations, is dosing. The correct weight-based dose of intramuscular midazolam has been subject to discussion ranging from 0.1 to 0.2 mg/kg4 5 26 and fixed doses of 5 mg for patients weighing from 13 to 40 kg and 10 mg above 40 kg 11 27 28. Incorrect weight-based dosing in the prehospital setting has been an important issue of concern for paramedics29 and in a recent study, a third of treated patients received an incorrect dose 30.…”
Section: Discussionmentioning
confidence: 99%
“…This has led to a change in clinical practice guidelines 31 32. While many prehospital providers, including Australian emergency medical service systems,26 are still limited to first-line BZD treatment only, levetiracetam and valproate are attractive alternatives to repeated BZD. Levetiracetam requires a 5 min intravenous infusion but has a favourable adverse event profile, while valproate can be given as an intravenous bolus but has some hypothetical concerns regarding use in young infants 33.…”
Section: Discussionmentioning
confidence: 99%
“…if >40 kg, and 5 mg if 13–40 kg, 9,17 which simplifies management, but may lead to wide variation in weight‐based dosages. A recent review found wide dosing variation in pre‐hospital services in Australia and New Zealand 18 . The heterogeneity of midazolam dosing and other AEDs could be useful to explore in high quality, adequately powered, prospectively collected observational data, and could provide evidence regarding the effectiveness of various dosages of midazolam for seizure cessation.…”
Section: Discussionmentioning
confidence: 99%
“…A recent review found wide dosing variation in pre-hospital services in Australia and New Zealand. 18 The heterogeneity of midazolam dosing and other AEDs could be useful to explore in high quality, adequately powered, prospectively collected observational data, and could provide evidence regarding the effectiveness of various dosages of midazolam for seizure cessation. Until recently, there was no highquality evidence on second-line AEDs for children with SE.…”
Section: Discussionmentioning
confidence: 99%
“…Ein bilateral tonisch-klonischer Anfall sollte spätestens nach 5 min Dauer durchbrochen werden. Bei einem fokalen Anfall sollte dies spätestens nach 10 min und bei Absence-Anfällen nach 10-15 min erreicht sein [10,17].…”
Section: Krampfanfälleunclassified